Editor's Choice – Bypass versus Angioplasty for Severe Ischaemia of the Leg (BASIL) Prospective Cohort Study and the Generalisability of the BASIL-2 Randomised Controlled Trial - Popplewell, Matthew A.; Meecham, Lewis; Davies, Huw O.B.; Kelly, Lisa; Ellis, Tracy; Bate, Gareth R.; Moakes, Catherine A.; Bradbury, Andrew W. (European journal of vascular and endovascular surgery, 2024)
The Bypass versus Angioplasty in Severe Ischaemia of the Leg-2 (BASIL-2) randomised controlled trial has shown that, for patients with chronic limb threatening ischaemia (CLTI) who require an infrapopliteal (IP) revascularisation a vein bypass (VB) first revascularisation strategy led to a 35% increased risk of major amputation or death when compared with a best endovascular treatment (BET) first revascularisation strategy. The study aims are to place the BASIL-2 trial within the context of the CLTI patient population as a whole and to investigate the generalisability of the BASIL-2 outcome data. This was an observational, single centre prospective cohort study. Between 24 June 2014 and 31 July 2018, the BASIL Prospective Cohort Study (PCS) was performed which used BASIL-2 trial case record forms to document the characteristics, initial and subsequent management, and outcomes of 471 consecutive CLTI patients admitted to an academic vascular centre. Ethical approval was obtained, and all patients provided fully informed written consent. Follow up data were censored on 14 December 2022. Of the 238 patients who required an infrainguinal revascularisation, 75 (32%) had either IP bypass (39 patients) or IP BET (36 patients) outside BASIL-2. Seventeen patients were initially randomised to BASIL-2. A further three patients who did not have an IP revascularisation as their initial management were later randomised in BASIL-2. Therefore, 95/471 (20%) of patients had IP revascularisation (16% outside, 4% inside BASIL-2). Differences in amputation free survival, overall survival, and limb salvage between IP bypass and IP BET performed outside BASIL-2 were not subject to hypothesis testing due to the small sample size. Reasons for non-randomisation into the trial were numerous, but often due to anatomical and technical considerations. CLTI patients who required an IP revascularisation procedure and were subsequently randomised into BASIL-2 accounted for a small subset of the CLTI population as a whole. For a wide range of patient, limb, anatomical and operational reasons, most patients in this cohort were deemed unsuitable for randomisation in BASIL-2. The results of BASIL-2 should be interpreted in this context.